Similar Aspects of English and Uzbek Literature - Abdullayeva Visola Sherali qizi (Researchparks Publishing, 2022)
The main purpose of the work is to compare the interpretation of the artistic world of childhood in American (Uzbek) and Uzbek literature, the peculiarities and commonalities between them. The analysis of the works of the famous poet and translator G. Gulam